2021
DOI: 10.21203/rs.3.rs-152629/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pathways to Seeking Treatment, Diagnose and Follow Up of Esophageal Cancer Patients in Arsi Zone, Oromia, Ethiopia: Qualitative Phenomenological Study

Abstract: Background:- Esophageal cancer patients experience multifaceted challenges but studies often focus on the prevalence and risk factors of esophageal cancer with no documentation of the lived experiences of patients. This study aimed at exploring the lived experiences of esophageal cancer patients with the concept of uncovering pathways to seeking treatment, diagnosis, and follow-up. Methods:- A qualitative phenomenological study was conducted from September 01 to October 30, 2019. Data were collected from 25 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Approximately 51.65% of the cases of esophageal cancer were females, while 48.35% were men. Nine out of the total articles reviewed reported a higher proportion (51.86% to 61.11%) of females with the disease, 51 , 54 , 55 , 57 , 59 , 61 , 63 - 65 whereas 8 studies reported that males were more commonly diagnosed with esophageal cancer, with the proportion ranging from 50.69% to 74.19%. 49 , 50 , 52 , 53 , 56 , 58 , 60 , 62 At the time of the initial diagnosis, the reported age range for the cases was 18 to 95 years old.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Approximately 51.65% of the cases of esophageal cancer were females, while 48.35% were men. Nine out of the total articles reviewed reported a higher proportion (51.86% to 61.11%) of females with the disease, 51 , 54 , 55 , 57 , 59 , 61 , 63 - 65 whereas 8 studies reported that males were more commonly diagnosed with esophageal cancer, with the proportion ranging from 50.69% to 74.19%. 49 , 50 , 52 , 53 , 56 , 58 , 60 , 62 At the time of the initial diagnosis, the reported age range for the cases was 18 to 95 years old.…”
Section: Resultsmentioning
confidence: 94%
“… 52 The patients’ median age was 55 (IQR: 19) years old, 56 according to 1 study. Five studies 50 , 51 , 55 , 56 , 59 did not disclose the age range of the patients, whereas 4 other studies 49 , 61 , 62 , 65 did not disclose the average age at the time of initial diagnosis ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations